Asbab Al-Nuzul : Antara Histori dan Historisitas Al-Quran - Midih Saputra (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
The science of asbab al-nuzul is one of the important methodological tools that supports the interpretation of the verses of the Qur'an which get a context horizon accompanying the decline of the verses of the Qur'an. The theme in the ulum al-Qur'an, asbab al-nuzul discusses outside the text. Asbab al-nuzul as one of the instruments for understanding the Qur'an. Quantitatively, the verses of the Qur'an which come down for certain reasons are not too many, Muslim scholars pay particular attention to these verses through discussion of the causes of the decline of the Qur'an. The existence of the science of Asbab al-nuzul is difficult to avoid from conflict of distinction (distance of the text and the interpreter) to explore and understand the meanings of the verses of the Qur'an. The debate between the generality of the text and the specificity of the causes or otherwise interesting from the asbab al-nuzul study. These two rules are very important in the process of exploring and constructing critical arguments which have implications for the status of stipulating a law.